Understanding the Importance of Attachment in Shame Traumatic Memory Relation to Depression: The Impact of Emotion Regulation Processes - Matos, Marcela (2013)
Early relationships are crucial to human brain maturation, well-being, affect regulation and self-other schema. Shame traumatic memories are related to psychopathology, and recent research has shown that the quality and type of attachment relationships may be crucial in shame traumatic memories in relation to psychopathology. The current study explores a mediator model of emotion regulation processes (rumination, thought suppression and dissociation) on the association between shame traumatic memory, with attachment figures and with others, and depressive symptoms.